PEMBENTUKAN KONSEP MANAJEMEN PERILAKU SISWA DALAM PROGRAM PENGALAMAN LAPANGAN PERTAMA MAHASISWA PENDIDIKAN MATEMATIKA [SHAPING THE CONCEPT OF STUDENTS’ BEHAVIOR MANAGEMENT IN THE FIRST FIELD EXPERIENCE PROGRAM FOR MATHEMATICS EDUCATION STUDENTS] - Melda Jaya Saragih (Universitas Pelita Harapan, 2019)
The Field Experience Program (PPL) is a holistic learning activity related to developing the competency of prospective Christian teachers based on the profile of a graduate of the mathematics education program at Universitas Pelita Harapan. The First Field Experience Program 1 (PPL 1) is the student's initial experience in school, namely the introduction and adaptation of prospective teachers with classes and the role of the teacher in the classroom. The purpose of this study was to explore the benefits of student teachers after the First Field Experince Program to students’ behaviour management through observation and reflection techniques. This study used qualitative descriptive methods, where data is collected through documentation (portfolios), open questionnaires and student reflections. There were 30 UPH mathematics education students as participants who spread across several Christian schools around the greater Jakarta area. The results of this study show that PPL 1 activities bring great benefits in forming the concept of correct behavior management where student teachers can view students as individuals who need to be guided in the right direction with love and realizing God loves them so much, students teacher know and recognize forms negative behavior of students in the classroom, and students teacher learn how to handle student behavior wisely. Student teachers also have clear commitments when they become teachers later.BAHASA INDONESIA ABSTRAK: Program Pengalaman Lapangan (PPL) adalah kegiatan pembelajaran holistis yang berkaitan dengan pengembangan kompetensi seorang calon guru Kristen sesuai dengan profil lulusan pendidikan matematika, UPH. Program Pengalaman Lapangan 1 (PPL 1) merupakan tahap awal pengalaman mahasiswa di sekolah, yaitu tahap pengenalan dan penyesuaian Mahasiswa guru dengan ruang kelas dan peranan guru dalam kelas. Adapun tujuan penelitian ini adalah untuk melihat seberapa besar manfaat yang didapatkan mahasiswa guru setelah kegiatan PPL 1 mengenai konsep manajemen perilaku siswa dalam kelas melalui teknik observasi dan refleksi. Penelitian ini menggunakan metode deskriptif kualitatif, dimana data dikumpulkan melalui dokumentasi (portfolio), angket terbuka dan refleksi mahasiswa. Partisipan terdiri dari 30 mahasiswa pendidikan matematika-UPH yang tersebar di beberapa sekolah Kristen di sekitar Jabodetabek. Hasil penelitian menunjukkan bahwa kegiatan PPL 1 ini membawa manfaat yang besar dalam pembentukan konsep manajemen perilaku yang benar dimana mahasiswa dapat memandang siswa sebagai pribadi perlu dituntun ke arah yang benar dengan penuh kasih serta Tuhan sangat mengasihi mereka, mahasiswa mengetahui dan mengenal bentuk-bentuk perilaku negatif siswa di dalam kelas, serta mahasiswa belajar cara menangani perilaku siswa dengan bijaksana. Mahasiswa guru juga memiliki komitmen yang jelas ketika mereka menjadi guru nantinya.